2020
DOI: 10.1002/dad2.12021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diversity on the measurement of functional impairment: An international validation of the Amsterdam IADL Questionnaire in eight countries

Abstract: Introduction To understand the potential influence of diversity on the measurement of functional impairment in dementia, we aimed to investigate possible bias caused by age, gender, education, and cultural differences. Methods A total of 3571 individuals (67.1 ± 9.5 years old, 44.7% female) from The Netherlands, Spain, France, United States, United Kingdom, Greece, Serbia, and Finland were included. Functional impairment was measured using the Amsterdam Instrumental Activities of Daily Living (IADL) Questionna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 54 publications
7
30
0
Order By: Relevance
“…The correlations between the A-IADL-Q-SV and the clinical measures of cognition and functioning were in the magnitude and direction as hypothesized and are, therefore, in line with previous studies [15,22]. However, we observed a moderate correlation between the A-IADL-Q-SV German and age, whilst the original A-IADL-Q and A-IADL-Q-SV observed small correlations [15,18,22]. Another study on the A-IADL-Q in Spain also observed a moderate correlation of the A-IADL-Q with age [45].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The correlations between the A-IADL-Q-SV and the clinical measures of cognition and functioning were in the magnitude and direction as hypothesized and are, therefore, in line with previous studies [15,22]. However, we observed a moderate correlation between the A-IADL-Q-SV German and age, whilst the original A-IADL-Q and A-IADL-Q-SV observed small correlations [15,18,22]. Another study on the A-IADL-Q in Spain also observed a moderate correlation of the A-IADL-Q with age [45].…”
Section: Discussionsupporting
confidence: 91%
“…The items flagged for DIF using a priori thresholds matched the items flagged using the Monte Carlo thresholds, providing support for the a priori thresholds. The findings of the DIF analysis agree with a previous investigation on item bias in eight Western countries, which indicated that the A-IADL-Q-SV was robust to cultural differences, as well as to age, sex and education [18].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The A-IADL-Q is aimed at assessing cognitively complex, relevant everyday activities [ 35 ]. It has been extensively validated [ 36 40 ]. Item scores range from 0 (no difficulty performing the activity) to 4 (unable to perform the activity), comparing current performance to the past.…”
Section: Methodsmentioning
confidence: 99%